Mechanism and physical activities in bone-skeletal muscle crosstalk - Zhao, Zhonghan; Yan, Kai; Guan, Qiao; Guo, Qiang; Zhao, Can (Frontiers in Endocrinology, 2024)
Bone and skeletal muscle work in coordination to maintain the function of the musculoskeletal system, in which skeletal muscle contraction drives the movement of the bone lever system while bone provides insert sites for skeletal muscle through the bone-muscle junction. Existing evidence suggests that factors secreted by skeletal muscle and bone mediate the interaction between the two tissues. Herein, we focused on the relationship between skeletal muscle and bone and the underlying mechanism of the interaction. Exercise can promote bone strength and secrete osteocalcin and insulin-like growth factor I into the blood, thus improving muscle quality. In addition, exercise can also promote myostatin, interleukin-6, Irisin, and apelin in muscles to enter the blood so that they can act on bones to maintain the balance between bone absorption and bone formation. There is a special regulatory axis interleukin-6/osteocalcin between myokines and osteokines, which is mainly influenced by exercise. Therefore, we pay attention to the important factors in the bone-muscle intersection that are affected by exercise, which were found or their functions were expanded, which strengthened the connection between organs of the whole body, highlighting the importance of exercise and contributing to the diagnosis, prevention, and treatment of osteoporosis and sarcopenia in the clinic.